Mangrove Ecosystem Resource Management Based on Silvofishery (The Case of RPH Tegal - Tangkil, KPH Purwakarta, Blanakan Subang East Java) - Ahmad Muhtadi; Kadarwan Soewradi; Taryono Taryono (Jurnal Perikanan dan Kelautan, 2017)
Silvofishery based mangrove ecosystem based resource management has been alreadywidely known and practiced, both at home and abroad. However, until now it’s difficultto find silvofishery application with correct and proper principles, in terms of bioengineering, ecological and institutional. The researched was conducted on March2012. The aims of this study were (1) assess the ecological status, (2) assess fishaquaculture bioengineering, (3) economic and financial analysis for the silvofisheryapplication, and (4) determine the pattern of silvofishery management in RPH TegalTangkil.Collected data were related to ecological, economic, social and institutionalaspect, which related to silvofishery management in RPH Tegal-Tangkil. The researchshowed that, mangroves contribute significantly to the daily shrimp by product. Waterquality conditions currently were still suitable for fish aquaculture activities. Althoughthere were discovered heavy metals content in this area, there for it is necessary toimprove water quality by develop reservoir system. In terms of bioengineering, fishermanwere still culture fish by traditionally technique and not done with correct and properprinciples. Economically silvofishery system was still able to develop for increasefishermans incomes. If silvofisheries were applied properly, it can increase fishermanincome up to 509.60%. However, silvofishery management was still deficient; It is seenfrom the difference between the ideal and reality. Institutional improvement minawanamanagement system at least focus on the improvement of the organization and rules ofthe game.